Strategi Pengembangan Bisnis Rest Area Silaing Bawah Kota Padang Panjang - Hasyim, M. Ardi Nupi; Rahayu, Agus; Dirgantari, Puspo Dewi (Universitas Batanghari Jambi, 2024)
The city of Padang Panjang has its own potential and uniqueness compared to other cities in West Sumatra. Supported by its beautiful natural potential, the City of Padang Panjang has several tourist attractions with quite good performance, including the Minangkabau Information and Culture Documentation Center (PDIKM), the Minang Fantasi Area (MIFAN). Providing a place to rest requires no small investment costs. This investment is needed to procure the basic infrastructure needed for resting places to be realized and operational. The basic infrastructure needed includes land, access roads, circulation, facilities, and utilities. In addition to investment in basic infrastructure procurement, operational costs are also required, which include costs for general expenditures, personnel expenditures, and maintenance expenditures. In order for the provision and management of rest areas to be sustainable, the planning and management of rest areas must be planned as efficiently and effectively as possible . The method used is qualitative or descriptive with a phenomenological approach with data triangulation. The results obtained are Based on the Cartesian SWOT diagram above, it is known that the lower Silaing rest area is in quadrant I, which means that the development strategy is SO, namely the strategy of using strengths to maximize existing opportunities. This strategy is also known as a growth oriented strategy, which is to support an aggressive growth policy. If you refer to this strategy, the Downtown Silaing Rest Area of Padang Panjang City improves the image of the rest area which makes the rest area get a good image from users.